1992
DOI: 10.1002/chin.199217195
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reactions with Diethyl Acetonedicarboxylate: Novel Synthesis of Pyrazolo(3,4‐d)pyridazine Derivatives.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Hydrazone 3 undergoes a smooth reaction with hydrazine hydrate to yield 4-(4-hydroxyphenyl-hydrazonopyrazolone 6 . The structure and the chemistry of such compounds have received considerable attention [ 20 , 21 , 22 ]. We have observed that 6 readily condenses with acetylacetone to yield the pyrazolo[1,5-a]pyrimidine 7 , which has the potential of existing in tautomeric form 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrazone 3 undergoes a smooth reaction with hydrazine hydrate to yield 4-(4-hydroxyphenyl-hydrazonopyrazolone 6 . The structure and the chemistry of such compounds have received considerable attention [ 20 , 21 , 22 ]. We have observed that 6 readily condenses with acetylacetone to yield the pyrazolo[1,5-a]pyrimidine 7 , which has the potential of existing in tautomeric form 8 .…”
Section: Resultsmentioning
confidence: 99%